Contemporary business communication - Ober, Scot, 1946- (Houghton Mifflin, 2001)
Understanding business communication. Work-team communication. Using technology to Access and share information. Writing with style: individual elements. Writing with style: overall tone. The process of writing. Routine messages. Persuasive messages...